The effectiveness and implementation of the BokSmart Safe Six Injury prevention programme - Sewry, Nicola Ann (Division of Exercise Science and Sports Medicine, 2019)
INTRODUCTION: Injury prevention programmes in rugby union are important to reduce the sport’s injury burden. The BokSmart Safe Six exercise-based injury prevention programme (“Safe Six”) was designed for this purpose. The programme incorporates six targeted exercises as a warm-up for rugby players. The effectiveness of the BokSmart Safe Six programme was assessed using the “Sequence of Prevention” Model. METHODS: The first study was a prospective cohort study using injury surveillance, of players at the South African Rugby (SA Rugby) Youth week tournaments. The study was conducted over six years to determine the injury incidence density (IID) youth players and also factors associated with the IID. The second study was a systematic review with the purpose of determining the effectiveness of exercise-based injury prevention interventions to reduce injury rates in collision sports. The next study was conducted over three years of SA Rugby Youth weeks and assessed the awareness of coaches and players of the BokSmart Safe Six following a targeted-marketing approach. This was followed by a study in which the BokSmart Safe Six programme was implemented in a cohort of apparently healthy non-rugby playing adults. The aim of this study was to determine the efficacy of the programme on injury risk profiles (Functional Movement Screening and Musculoskeletal Screening Assessments). The final study was a cluster-randomised controlled trial (cRCT) over eight weeks, using six schools (n = 210 players) in the Western Cape to determine the effectiveness of the BokSmart Safe Six on injury risk profiles and IID. RESULTS AND CONCLUSIONS: SA youth rugby cohort have a similar IID to other youth rugby cohorts (and in some instances lower). The systematic review identified only one highlevel study (out of three) that was effective for injury prevention. The players’ awareness of the BokSmart Safe Six was associated with the awareness of their specific coaches’ awareness. The awareness increased during the targeted marketing approach. The BokSmart Safe Six was associated with minimal significant improvements of the injury risk profiles in both the healthy adults and in the cRCT intervention group youth rugby players.